2003
DOI: 10.1152/ajpgi.00423.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic glutathione and nitric oxide are critical for hepatic insulin-sensitizing substance action

Abstract: We tested the hypothesis that hepatic nitric oxide (NO) and glutathione (GSH) are involved in the synthesis of a putative hormone referred to as hepatic insulin-sensitizing substance HISS. Insulin action was assessed in Wistar rats using the rapid insulin sensitivity test (RIST). Blockade of hepatic NO synthesis with N(G)-nitro-l-arginine methyl ester (l-NAME, 1.0 mg/kg intraportal) decreased insulin sensitivity by 45.1 +/- 2.1% compared with control (from 287.3 +/- 18.1 to 155.3 +/- 10.1 mg glucose/kg, P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 36 publications
2
89
1
1
Order By: Relevance
“…Other studies by our groups [34,35] have previously uncovered other steps of the hepatic pathway that lead to HISS release. According to these studies, following a meal, the activation of the hepatic parasympathetic nerves leads to the release of acetylcholine, which binds to muscarinic receptors in the liver.…”
Section: Hepatic Parasympathetic Nerves Dysfunction and The Developmementioning
confidence: 96%
“…Other studies by our groups [34,35] have previously uncovered other steps of the hepatic pathway that lead to HISS release. According to these studies, following a meal, the activation of the hepatic parasympathetic nerves leads to the release of acetylcholine, which binds to muscarinic receptors in the liver.…”
Section: Hepatic Parasympathetic Nerves Dysfunction and The Developmementioning
confidence: 96%
“…Recent studies, however, have suggested the possibility that some NO may escape inactivation by traveling in a plasma compartment in the blood and act as an endocrine factor distal to the site of its release (17,18). Furthermore, it has been suggested that under hyperinsulinemic conditions, NO action in the liver can alter the release of a humoral factor, which increases nonhepatic glucose disposal (19,20). This mechanism may involve parasympathetic input as the effect is blocked by surgical liver denervation and atropine and is restored by acetylcholine administration (21,22).…”
mentioning
confidence: 99%
“…Alcohol suppresses the release or action of HISS and meal-induced insulin sensitization in rats [65]. Moreover, in animal models, acute alcohol administration also reduces glutathione [66] which is important for HISS release [67]. As with acute alcohol consumption, hepatic glutathione and HISS seem to be involved.…”
Section: Alcohol Consumption and Risk Of T2dmmentioning
confidence: 99%